A weighted method for estimation of receptor occupancy for pharmacodynamic measurements in drug development. Issue 2 (31st August 2015) - Sternebring, Ola; Alifrangis, Lene; Christensen, Toke Folke; Ji, Hong; Hegelund, Anne Charlotte; Högerkorp, Carl‐Magnus
Abstract : Background: Flow cytometry‐based receptor occupancy (RO) assessments for pharmacodynamic (PD) response measurements along with drug pharmacokinetic (PK) measurements represent a cornerstone in mechanism based PK/PD modeling of drugs against cell surface targets. This report describes the utility of using a "Free" and a "Bound" assay in combination to derive RO estimations through a weighted calculation method. Methods: Data from a RO assay validation study in human samples was used to explore the performance of various RO data calculation methods. The calculation methods were subsequently applied to investigate the best method to generate RO data in a first in human phase 1 clinical trial. Finally, the outcome of the analysis was used for PK/PD modeling of a prospective phase 2a trial. Results: The validation data assessment demonstrated that a weighted RO calculation method had a better performance in terms of precision, accuracy and dynamic range. In the phase 1 clinical trial data analysis the weighted method again demonstrated a better performance resulting in a more robust RO estimation, and subsequently also generating a more reliable PK/PD simulation for the phase 2a trial. Conclusions: This report demonstrated the utility of using a combined "Free" and "Bound" RO assessment together with a weighted calculation method to better support mechanism‐based PK/PD modeling activities. © 2015 International Clinical Cytometry Society